Profit Plan Analysis In Steam Alvaro Car Wash Business Bengkulu City - Apriyadi, Apriyadi; Yulianti, Oni; Irwanto , Tito (Universitas Dehasen Bengkulu, 2022)
The purpose of this study was to determine the profit planning analysis on the Steam Alvaro Car Wash Business in Bengkulu City. The analytical method used is Break Even Point analysis. The results of the research show that the break even point in 2021 was reached by washing 2,083 cars or IDR 104,747,664. The profit contribution rate is IDR 564,629,371, - or 5,566 cars with a contribution ratio of 53.8%. The level of security or the margin of safety is 63.07%. The company's profit rate reached 33.93%. Based on the 2021 break even point, a profit plan can be prepared for 2022. If the Steam Alvaro Car Wash Business in Bengkulu City plans a profit increase of 10% from 2021, which is Rp. 103,048,000, - then the washing level that must be achieved is Rp. 297,360. 749, - or 5,914 cars.